2021
DOI: 10.3390/foods10010146
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Aging Methods on the Formation of Aroma Volatiles in Beef Strip Loins

Abstract: This study investigated the effects of different aging methods on the changes in the concentrations of aroma volatiles of beef. One half (n = 15) of the beef strip loins were dry-aged, and the other half were wet-aged, and both aging processes continued for 28 days. The aroma volatiles from dry- and wet-aged samples were analyzed at seven-day intervals (n = 3 for each aging period). As the aging period increased, dry-aged beef showed higher concentrations of volatile compounds than those in wet-aged beef (p &l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…As shown in Figure 2 , after 42 days of traditional dry-ageing, dramatic increasing trends were detected in aldehydes (3-methylbutanal, 2-methylbutanal, benzene acetaldehyde, E-2-heptenal, nonanal, octanal, heptanal, and pentanal), ketones (2-heptanone), alcohols (1-octene-3-ol, pentanol, 2-methylpropanol, and ethanol), furans (2-pentylfuran), and esters (butyl acetate and butyl propanoate). Similarly, Lee et al [ 29 ] and Li et al [ 30 ] reported that dry-ageing increased concentrations of aldehydes, ketones, and alcohols. 3-methylbutanal (malty odor), 2-methylbutanal (chocolate odor), and benzene acetaldehyde (rosy odor) come from the Strecker degradation of leucine, isoleucine, and phenylalanine, respectively [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 86%
“…As shown in Figure 2 , after 42 days of traditional dry-ageing, dramatic increasing trends were detected in aldehydes (3-methylbutanal, 2-methylbutanal, benzene acetaldehyde, E-2-heptenal, nonanal, octanal, heptanal, and pentanal), ketones (2-heptanone), alcohols (1-octene-3-ol, pentanol, 2-methylpropanol, and ethanol), furans (2-pentylfuran), and esters (butyl acetate and butyl propanoate). Similarly, Lee et al [ 29 ] and Li et al [ 30 ] reported that dry-ageing increased concentrations of aldehydes, ketones, and alcohols. 3-methylbutanal (malty odor), 2-methylbutanal (chocolate odor), and benzene acetaldehyde (rosy odor) come from the Strecker degradation of leucine, isoleucine, and phenylalanine, respectively [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 86%
“…In addition, the high activity of the enzymes catalyzed by the abused temperature may accelerate the formation of VBN ( Tak et al, 2005 ). Furthermore, ice crystals formed in FT and AFT can induce the release of enzymes, leading to an increase in protein degradation ( Lee et al, 2021 ). Therefore, both abuse prior to freezing and during thawing at room accelerated the formation of VBN when compared to no temperature abuse.…”
Section: Resultsmentioning
confidence: 99%
“…To identify the differences in metabolites among storage methods, a partial least squares-discriminant analysis (PLS-DA) containing variable importance in projection (VIP) scores within the model were performed using MetaboAnalyst 4.0, according to Lee et al (2021) . The samples were log-transformed and autoscaled before conducting our multivariate analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Aldehydes mainly come from oxidation of fat and degradation of amino acids by Strecker (Lee et al., 2021). Most of aldehydes consisting of butyral, hexanal, heptanal, benzaldehyde, benzeneacetaldehyde, nonanal, and decanal which show feature fruity and creamy aroma.…”
Section: Resultsmentioning
confidence: 99%
“…Aldehydes mainly come from oxidation of fat and degradation of amino acids by Strecker (Lee et al, 2021). Most of aldehydes consisting of butyral, hexanal, heptanal, Abbreviations: "-" not detected; HAD, hot air drying; MD, microwave drying; SMIRD, short-and medium-wave infrared drying; VFD, vacuum freeze drying.…”
Section: Aldehydesmentioning
confidence: 99%